Analysis of Curriculum Changes and Their Impact on Student Learning Outcomes - Sufitri, Gita; Tajudding, Mawaddah; HM, Muliyana; Bakar, Abu (DIDAKTIKA, 2023)
This study aims to find out: how the influence of curriculum changes on improving the quality of education at MA DDI Massenreng Pulu, how to implement the curriculum at MA DDI Massenreng Pulu, how to evaluate the curriculum at MA DDI Massenreng Pulu. This study uses qualitative research with qualitative descriptive methods by collecting data using observation, interview and data analysis methods.the results of the study found that curriculum changes have a significant influence on improving the quality of education with the hope that with curriculum changes can improve the quality of learning and a better learning process so that the quality of education will also increase.